Does Enforcement Reduce Voluntary Tax Compliance? - Lederman, Leandra (2018)
Governments generally use enforcement methods, such as audits and the imposition of penalties, to deter noncompliance with tax laws. Although this approach is consistent with most economic modeling of tax compliance, some scholars caution that enforcement may backfire, “crowding out” taxpayers’ intrinsic motivations to pay taxes to such an extent that they reduce their tax payments. This Article analyzes the existing evidence to determine if this occurs. In fact, field studies suggest that enforcement tools, such as audits, are very effective deterrents. A few recent studies have found that audits have a negative effect on the subsequent tax payments of those found compliant on audit. This outcome, while perhaps initially surprising, is consistent with the deterrence model; a favorable outcome after audit may lower that taxpayer’s perceived likelihood of subsequent audit and the perceived magnitude of any sanction